Alih Kode dalam Komunikasi Lisan Peserta Workshop Pengabdian kepada Masyarakat Berbasis Participatory Action Research (PAR) Dosen PTAI se-Karesidenan Besuki, 26–28 Mei 2005: Code-Switching in the Oral Communication of Participants in the Community Service Workshop Based on Participatory Action Research (PAR) for Islamic Higher Education Lecturers in the Besuki Residency, May 26–28, 2005 - Abd. Rahman Ds (Fenomena, 2005)
Code-switching in multilingual academic settings remains underexplored, particularly in community service training within Indonesia’s higher education. This study examines the forms and triggers of code-switching in oral communication among bilingual/multilingual lecturers during a Participatory Action Research (PAR) workshop in Jember (May 26–28, 2005). Using descriptive qualitative methods—observation and interviews—the data were analyzed through discourse analysis. Findings reveal eight code-switching forms, predominantly Indonesian-to-Javanese, followed by Madurese, Bugis, English, and Arabic. These shifts are driven by social solidarity, respect, social class, topic choice, cultural distance, regional dialect, and intimacy. The study concludes that code-switching functions as a strategic tool for politeness and solidarity. Recommendations include fostering more inclusive, Indonesian-based academic interactions to enhance campus harmony. Fenomena alih kode dalam komunikasi lisan di lingkungan akademik multibahasa masih jarang diteliti, khususnya pada pelatihan pengabdian masyarakat perguruan tinggi agama Islam. Penelitian ini bertujuan mengidentifikasi bentuk dan faktor penyebab alih kode dalam komunikasi lisan dosen bilingual/multilingual pada workshop Participatory Action Research (PAR) di Jember (26–28 Mei 2005). Melalui metode deskriptif kualitatif dengan observasi dan wawancara, data dianalisis menggunakan pendekatan analisis wacana. Hasil penelitian menemukan delapan bentuk alih kode, dengan alih kode dari bahasa Indonesia ke bahasa Jawa sebagai yang paling dominan, diikuti Madura, Bugis, Inggris, dan Arab. Faktor penyebabnya meliputi solidaritas sosial, rasa hormat, kelas sosial, pilihan topik, jarak budaya, dialek regional, dan keakraban. Kesimpulannya, alih kode berfungsi sebagai strategi kesantunan dan solidaritas. Rekomendasi penelitian ini mendorong terciptanya interaksi akademik berbasis bahasa Indonesia yang santun demi keharmonisan kampus.